2022
DOI: 10.3390/ijms23137040
|View full text |Cite
|
Sign up to set email alerts
|

LAM Cells as Potential Drivers of Senescence in Lymphangioleiomyomatosis Microenvironment

Abstract: Senescence is a stress-response process characterized by the irreversible inhibition of cell proliferation, associated to the acquisition of a senescence-associated secretory phenotype (SASP), that may drive pathological conditions. Lymphangioleiomyomatosis (LAM) is a rare disease in which LAM cells, featuring the hyperactivation of the mammalian Target of Rapamycin Complex 1 (mTORC1) for the absence of tuberin expression, cause the disruption of the lung parenchyma. Considering that LAM cells secrete SASP fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…How TSC cysts prime their microenvironment to encourage and support growth is an emerging area. In the lung setting, TSC/LAM cells have been shown to induce senescence in neighbouring cells in a paracrine manner (Bernardelli et al., 2022 ). In a TSC renal cyst mouse model and TSC neural mouse model, wild‐type cells of the microenvironment were observed to take on an EV‐mediated Tsc2 ‐mutant disease phenotype (Kumar et al., 2021 ; Patel et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…How TSC cysts prime their microenvironment to encourage and support growth is an emerging area. In the lung setting, TSC/LAM cells have been shown to induce senescence in neighbouring cells in a paracrine manner (Bernardelli et al., 2022 ). In a TSC renal cyst mouse model and TSC neural mouse model, wild‐type cells of the microenvironment were observed to take on an EV‐mediated Tsc2 ‐mutant disease phenotype (Kumar et al., 2021 ; Patel et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in other respiratory disease such as IPF, senescence might drive the progressive loss of parenchymal structure in LAM which ultimately causes the impairment of lung function ( 51 ). It has been demonstrated that LAM cells secrete molecules known to be SASP components comprised metalloproteinases ( 52 ), proinflammatory cytokines IL-6 ( 53 ) and IL-8 ( 50 ), kathepsin K ( 54 ), and VEGF-D ( 39 ) reinforcing the hypothesis of a LAM cell communication with the microenvironment and a SASP modulation of the remodeling of the lung parenchyma. Interestingly, IL-8, a potent neutrophil chemotactic factor that triggers chemotaxis and neutrophil activation through a phosphorylation cascade in the inflammatory response ( 55 ), has been demonstrated to be involved in the pathogenesis and progression of lung diseases such as ARDS and SARS CoV-2, suggesting the possibility to use IL-8 as a biomarker or as a therapeutic target ( 56 ).…”
Section: Lam and Mtormentioning
confidence: 90%
“…We recently demonstrated that LAM/TSC cells, derived by chylous thorax of a LAM/TSC patient, have senescent features dependent from mTOR hyperactivation and the capability to induce senescence in neighboring cells ( 50 ). As demonstrated in other respiratory disease such as IPF, senescence might drive the progressive loss of parenchymal structure in LAM which ultimately causes the impairment of lung function ( 51 ).…”
Section: Lam and Mtormentioning
confidence: 99%
“…In all the experiments, TSC2 -/meth cells were cultured for 3 up to 5 passages (meaning for about 20 days after the thawing), as we previously described [ 22 ]. This precaution allowed us to maintain and standardize the primary features of these cells.…”
Section: Methodsmentioning
confidence: 99%